Consumers' choices among alternative electricity programmes in Geneva – an empirical analysis. (6th August 2009) - Weber, Sylvain; Baranzini, Andrea; Fragniere, Emmanuel
Services Industriels de Geneve (SIG) is a monopoly which delivers natural gas, water and electricity in the Canton of Geneva (Switzerland). A few years ago, SIG offered to Geneva households the possibility to choose among six different types of electricity products. The new electricity products differ particularly because of the origin of their production (natural gas, hydraulic, solar, etc.) and their prices. Through a survey research, we collected information about the households' choices among the different electricity products. By a series of logistic regressions, we assess what determines households' knowledge of the different electricity products which are offered by SIG, as well as the factors explaining their choices.